Dominant Religion, Radical Right-Wing, and Social Trust: An Empirical Investigation - Nazlı Keyifli; Jinyoung Hwang; Sacit Hadi Akdede (Journal of Economy Culture and Society)
This paper empirically investigates the impact of dominant religion and radical right-wing political views on social trust, using data taken from the World Values Survey on 60 countries over the period 2010–2014. To supplement the existing literature, we consider both religion and political views at the same regression equation, and relatively recent data to reflect terrorism and anti-immigration policies in recent years. It is found that people living in Asian countries where Buddhism, Confucianism, Hinduism, and Shintoism are the dominant religions trust others more than people living in Christian and Muslim countries. A plausible explanation is that Asian religions are closely related to the ethics of life regarding relations with neighbors, which may have a positive impact on trust among people. However, when classified according to the frequency of participation in prayer, it is observed that these religions may not have a distinctly discriminatory impact on social trust. The impact of radical right-wing political views on trust is negative and statistically significant, meaning that people with radical right-wing political views have a relatively lower social trust than others. The empirical results suggest that religion and political views influence trust and can be a factor in producing either harmony or division among people.